Multiplatform Use-After-Free and Double-Free Detection in Binaries* - Grigor S. Keropyan; Vahagn G. Vardanyan; Hayk K. Aslanyan; Shamil F. Kurmangaleev; Sergey S. Gaissaryan (Изд-во НАН РА)
Use-after-free (UAF) defects are a class of memory corruption bugs, which occur when a program continues to use a pointer after it has been freed. Double-free (DF) defects arise when the same memory is freed more than once. The developed platform is capable to analyze binaries of several architectures (x86, x86-64, MIPS, POWER-PC, ARM) and is based on program static analysis approach. For program analysis SDG (System Dependence Graph) machine-independent representation is used. SDG combines call graph, control and data flow graphs of the program.
Keywords: Mathematics